the gun report and showreel of the year - Gunn, Donald (Suffolk: FlaxmanWike, 2005)
Contents: The showreel of the year 2005. Showreel index. The world's most awarded print 2005. Guest essays. Student competitions
Incluye seven year consolidated tables 1999-2005
Keywords: Publicidad - Gunn Report